Frailty transitions, inflammation, and mortality among persons aging with HIV infection and injection drug use. (1st July 2020) - Piggott, Damani A.; Bandeen-Roche, Karen; Mehta, Shruti H.; Brown, Todd T.; Yang, Huanle; Walston, Jeremy D.; Leng, Sean X.; Kirk, Gregory D.
Abstract : Objective: Frailty is a critical aging-related syndrome marked by diminished physiologic reserve and heightened vulnerability to stress, predictive of major adverse clinical outcomes in HIV-infected and uninfected adults. Frailty is a dynamic state, yet little data exist on predictors and consequences of frailty transitions. Design/methods: Frailty was assessed semiannually among HIV-infected and uninfected persons with prior injection drug use using the five Fried phenotype domains. An inflammatory index score was constructed from IL-6 and soluble TNF-α receptor-1 data. Markov transition models assessed determinants of frailty transitions. Cox proportional hazards models estimated mortality risk. Results: Among 1353 AIDS Linked to the IntraVenous Experience participants with 9559 frailty transition assessments, 33% were HIV-infected. Younger age, higher education, employment, reduced comorbidity, HIV virologic suppression, elevated CD4 + nadir (>500 cells/μl) and absence of a prior AIDS diagnosis were significantly associated with both reduced frailty progression and greater frailty recovery. Each SD decrease in inflammatory index score was associated with decreased frailty progression [odds ratio 0.78; 95% confidence interval (CI), 0.65, 0.92] and increased frailty recovery (odds ratio 1.29; 95% CI, 1.08, 1.53). Being frail at one of two consecutive visits was associated with increased mortality, compared with maintenance of a nonfrail state. Being frail at both of two consecutive visits demonstrated the highest mortality risk (hazard ratio 3.23; 95% CI, 2.1, 4.96). Conclusion: Sustained, and to a lesser degree, intermittent frail states are associated with increased mortality. HIV virologic suppression with earlier antiretroviral therapy, reduced comorbidity, and reduced inflammation may prevent frailty progression and promote frailty recovery, consequently improving survival for persons aging with HIV and persons with prior injection drug use. Abstract : Supplemental Digital Content is available in the text